Bawić się słowami, czyli jak uczyć języka ojczystego i obcego dzieci z dysleksją rozwojową - Misztal, Barbara (Dydaktyka Polonistyczna, 2015)
The process of learning and teaching has the best effects while children explore and play and it is a great challenge for them. Nevertheless, there are many problems and obstacles due to the great differences between the levels of students’ language competency. Children with dyslexia, a specific learning difficulty, need additional support. Nowadays some parents and teachers often lack sufficient understanding of the nature of dyslexia and they don’t believe in students’ achievement. The article presents a large number of interesting methods and proposals of games on Polish and English lessons and schools clubs as well in order to help students with dyslexia to learn with better results. All the ideas are based on brain friendly learning principles and the theory of multiple intelligences.